Exploring Bintan Island Through Travel Photography - Zenith Halalan; Riswel Zam; Ferli Mulianto Pratama (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Travel photography is not merely about documenting spaces and events, but also representing the experiences, culture, and social interactions of a region. This creative research explores Bintan Island through a travel photography approach, presenting natural landscapes, coastal communities, and cultural and spiritual dimensions. The methods applied include preparation, exploration, experimentation, and completion stages. Data was collected through observation and interviews, while the creative process was based on basic photography theory, feature photography, documentation, photo stories, ethnography, and human interest. The resulting work consists of five photographs in three categories: natural landscapes, portraits of social interactions, and local culture. Technically, slow speed and stop action techniques, wide-angle lenses, exposure settings, and GND and CPL filters were used for tonal balance. The results confirm that travel photography can be a narrative medium that captures visual beauty as well as social dynamics, landscape changes, and the spiritual values of coastal communities.